Rugged High-Entropy Alloy Nanowires with in Situ Formed Surface Spinel Oxide As Highly Stable Electrocatalyst in Zn–Air Batteries - Jin, Zeyu; Lyu, Juan; Zhao, Yi-Lu; Li, Huanglong; Lin, Xi; Xie, Guoqiang; Liu, Xingjun; Kai, Ji-Jung; Qiu, Hua-Jun (ACS materials letters, 2020)
Noble metal elements are the key to many high-performance heterogeneous catalytic processes; nevertheless, how to reduce the usage of such scarce and prohibitive materials while maintaining or even enhancing the desired catalytic performance has always been a grand challenge. In this work, we introduce a general dealloying procedure to synthesize a series of predesigned rugged high-entropy alloy (HEA) nanowires, including Al–Ni–Co–Ru–X, where X = Mo, Cu, V, Fe as the trifunctional electrocatalysts for the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and oxygen reduction reaction (ORR). These mechanically and chemically stable HEAs can not only significantly reduce the noble-metal contents but also effectively enhance the flexibility in their electronic structures suitable for broad catalytic functionalities. Specifically, our etched Al–Ni–Co–Ru–Mo nanowires exhibit a similarly high electrocatalytic activity as commercial Pt/C for HER. Its OER activity is much higher than the commercial RuO2 and among the highest ever-reported Ru-based OER catalysts. Its ORR catalytic activity is even higher than Pt/C, although Ru is not considered as a good ORR catalyst. Moreover, the oxidized surfaces of these HEAs are highly stable during continuous working conditions, which is crucial for overall water splitting and rechargeable Zn–air batteries.